(untitled) (REMUNOM, 2023)
The present work investigated the processes of literacy and literacy that occurred during the COVID-19 pandemic through some selected and analyzed articles that spoke to our objectives, within the time frame from 2019 to 2023. Starting from a cultural socio-historical view, we know that learning is a result, among other aspects, of exposure to the cultural universe and mediated by a more experienced person. Much has been discussed about the pedagogical efforts of teachers in the sense of reinventing their practice to acquire skills and competences so that their students could become literate through technological resources. In this sense, we sought in a qualitative perspective, through a bibliographic review of some experience reports, to highlight the experiences of teachers, observing their pedagogical difficulties, in order to find elements that verify the development of students in this scenario of social distancing. In addition, to elucidate reading practices in remote teaching, within a context of scientific and technological literacy in basic education, and also to seek to understand how technology contributed to the teaching-learning process, and how this context impacted the actions carried out by teachers of basic education. The results show that mere access to resources and technologies was not enough to guarantee learning situations, with the teacher’s role being relevant, as a mediator, in the literacy and literacy processes.